A systematic review of psychological difficulties among elite sports coaches - Kang, S.; Lee, S. (Frontiers in Psychology, 2025)
Introduction: This systematic review examined the psychological difficulties experienced by elite sports coaches, focusing on their causes, consequences, and potential interventions. Despite increasing recognition of the challenges faced by coaches, limited attention has been paid to understanding their psychological difficulties and available support systems.